2019
DOI: 10.1037/ocp0000139
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sleep on workplace cognitive failure and safety.

Abstract: Healthy employee sleep is important for occupational safety, but the mechanisms that explain the relationships among sleep and safety-related behaviors remain unknown. We draw from Crain, Brossoit, and Fisher’s (in press) work, nonwork, and sleep (WNS) framework and Barnes’ (2012) model of sleep and self-regulation in organizations to investigate the influence of construction workers’ self-reported sleep quantity (i.e., duration) and quality (i.e., feeling well-rest upon awakening, ability to fall asleep and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 84 publications
4
66
0
1
Order By: Relevance
“…Good sleep provides physical energy that is needed for waking physical and cognitive activities. Brossoit and colleagues [13] could confirm the model by showing that sleep quantity and quality affect cognitive failure that in turn affects safety-related behaviour. According to Martin [20], workplace cognitive failure can best be defined as a "cognitively based error that occurs during the performance of a task that the person is normally successful in executing" (p. 97).…”
Section: Delayed Sleep Onset and Shorter Sleep Duration Under The Magmentioning
confidence: 89%
See 1 more Smart Citation
“…Good sleep provides physical energy that is needed for waking physical and cognitive activities. Brossoit and colleagues [13] could confirm the model by showing that sleep quantity and quality affect cognitive failure that in turn affects safety-related behaviour. According to Martin [20], workplace cognitive failure can best be defined as a "cognitively based error that occurs during the performance of a task that the person is normally successful in executing" (p. 97).…”
Section: Delayed Sleep Onset and Shorter Sleep Duration Under The Magmentioning
confidence: 89%
“…Many errors at work occur during routine task fulfillment and point to attentional slips or loss of working memory contents [10]. Such workplace cognitive failure has been consistently shown to be an antecedent of near accidents during the commute to work and back home [11,12] and to predict minor injuries at work [13], during sports after work [14] and domestic falls [15]. Hence, we hypothesised more frequent workplace cognitive failure on Monday morning compared to the subsequent working weekdays (Monday Effect; hypothesis 1 (H1)).…”
Section: Introductionmentioning
confidence: 99%
“…This result was consistent with outcomes of other studies, which report that employees with sleep disorders and EDS have poorer safety behaviors, less safety participation, and pose higher risks to safety compliance. 19,42,43 The relationship between sleep and safety-related behavior is complex and its mechanism is unknown. 42 It has been suggested that sleep disorders can increase unethical behavior in employees through diminishing self-control resources; 44 there is some evidence that EDS can reduce safety behavior through tiredness and losing focus.…”
Section: Discussionmentioning
confidence: 99%
“…19,42,43 The relationship between sleep and safety-related behavior is complex and its mechanism is unknown. 42 It has been suggested that sleep disorders can increase unethical behavior in employees through diminishing self-control resources; 44 there is some evidence that EDS can reduce safety behavior through tiredness and losing focus. 45 In addition, insomnia and other sleep disorders are known to reduce participation in social activities.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the construction project (e.g., residential, roads, bridges), workers are exposed to varying hazards, such as working at height or operating complex machinery (Buckley et al, 2016), and often have to work in close proximity to one another, performing different SAFETY TRAINING FOR MIGRANT CONSTRUCTION WORKERS workers, influenced by work-related experiences, and safety practices in their countries of origin (Brunette, 2004). In addition, malnourishment and cramped living conditions contribute to sleep deprivation, increased fatigue and poor concentration, reducing safetyrelated behaviors on site and enhancing the risk of accident and injury (Brossoit et al, 2018;Dutta, 2017;Kao, Spitzmueller, Cigularov, & Wu, 2016). The situation is particularly dire for migrants who have entered the country illegally, as they fear losing their jobs or being deported (Menzel & Gutierrez, 2010;Moyce & Schenker, 2018).…”
mentioning
confidence: 99%